2013
DOI: 10.2527/jas.2012-5317
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of total body water and water intake in Shetland ponies measured by an isotope dilution technique1

Abstract: Water is an essential nutrient necessary to support life, and adequate water supply is crucial for animal survival and productivity. The present study was designed to determine seasonal changes in the water metabolism of horses under outdoor conditions. Total body water (TBW) and total water intake (TWI) of 10 adult Shetland pony mares were estimated at monthly intervals for 14 mo by using the deuterium dilution technique. During the last 4 mo, 5 ponies were fed restrictively to simulate natural feed shortage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…Our results showed that all mean physiological parameters (heart rate, respiratory rate, pulse and rectal temperature) were tendentially increased in summer in comparison to winter season ( Table 1 ). The results of increased heart rate in summer in the present study is in agreement with Brinkmann et al [17] , [18] , although the differences between summer and winter heart rate values were less obvious in our study than that reported by Brinkmann et al (Mean heart rate: summer (58/beats/m), winter (35 beats/m)) [19] . In agreement with Scheibe et al [20] , increased heart rate in summer may indicate the adaptation ability of Shetland pony to hot temperatures [20] for body temperature regulation.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that all mean physiological parameters (heart rate, respiratory rate, pulse and rectal temperature) were tendentially increased in summer in comparison to winter season ( Table 1 ). The results of increased heart rate in summer in the present study is in agreement with Brinkmann et al [17] , [18] , although the differences between summer and winter heart rate values were less obvious in our study than that reported by Brinkmann et al (Mean heart rate: summer (58/beats/m), winter (35 beats/m)) [19] . In agreement with Scheibe et al [20] , increased heart rate in summer may indicate the adaptation ability of Shetland pony to hot temperatures [20] for body temperature regulation.…”
Section: Discussionsupporting
confidence: 92%
“…The range in average monthly temperature over the year at both training centres was about 23 °C, with the highest temperatures in August and the lowest in January. The horses were stabled at the ambient temperature, so the high temperatures in summer may have increased their metabolic rate and the low temperatures in winter may have reduced it, which would be consistent with the results of previous studies [ 8 , 29 , 30 ]. Although a long photoperiod induces a higher metabolic rate than a shorter photoperiod in rats and cats [ 9 , 31 ], there are no published studies, to our knowledge, on the direct relationship between photoperiod and energy expenditure by horses.…”
Section: Discussionsupporting
confidence: 90%
“…Observed intakes range from 5.1 L/100kg BW 29 to 6.9 L/100kg BW 30 in pregnant mares and from 11.9 L/100kg BW to 13.9 L/100kg BW in lactating mares 1 and are influenced by several factors, including DMI and environmental temperature. Availability of water is especially important for horses consuming dried preserved forage, such as during cold seasons and when stalled 31,32 . Water restriction during pregnancy results in decreased feed intake and loss of BW 30 .…”
Section: Vitamins Minerals and Water Requirements And Recommendationsmentioning
confidence: 99%